Effects of phosphonium-based ionic liquids on phospholipid membranes studied by small-angle X-ray scattering - Kontro, Inkeri; Svedström, Kirsi; Duša, Filip; Ahvenainen, Patrik; Ruokonen, Suvi-Katriina; Witos, Joanna; Wiedmer, Susanne K (Chemistry and physics of lipids, 2016)
The effects of ionic liquids on model phospholipid membranes were studied by small-angle X-ray scattering, dynamic light scattering (DLS) and zeta potential measurements. Multilamellar 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine liposomes and large unilamellar vesicles composed of l-α-phosphatidylcholine (eggPC) and l-α-phosphatidylglycerol (eggPG) (80:20mol%) or eggPC, eggPG, and cholesterol (60:20:20mol%) were used as biomimicking membrane models. The effects of the phosphonium-based ionic liquids: tributylmethylphosphonium acetate, trioctylmethylphosphonium acetate, tributyl(tetradecyl)-phosphonium acetate, and tributyl(tetradecyl)-phosphonium chloride, were compared to those of 1-ethyl-3-methyl-imidazolium acetate. With multilamellar vesicles, the ionic liquids that did not disrupt liposomes decreased the lamellar spacing as a function of concentration. The magnitude of the effect depended on concentration for all studied ionic liquids. Using large unilamellar vesicles, first a slight decrease in the vesicle size, then aggregation of vesicles was observed by DLS for increasing ionic liquid concentrations. At concentrations just below those that caused aggregation of liposomes, large unilamellar vesicles were coated by ionic liquid cations, evidenced by a change in their zeta potential. The ability of phosphonium-based ionic liquids to affect liposomes is related to the length of the hydrocarbon chains in the cation. Generally, the ability of ionic liquids to disrupt liposomes goes hand in hand with inducing disorder in the phospholipid membrane. However, trioctylmethylphosphonium acetate selectively extracted and induced a well-ordered lamellar structure in phospholipids from disrupted cholesterol-containing large unilamellar vesicles. This kind of effect was not seen with any other combination of ionic liquids and liposomes.
Keywords: maloúhlový rozptyl; Scattering, Small Angle; Organophosphorus Compounds; Liposomes; Unilamellar Liposomes; cholesterol; fosfolipidy; Cholesterol; dynamický rozptyl světla; liposomy; unilamelární lipozómy; difrakce rentgenového záření; Dynamic Light Scattering; Phospholipids; X-Ray Diffraction; iontové kapaliny; organofosforové sloučeniny; Ionic Liquids